Study of Photography Result using Blind Test Method - Ricky Ricky; Tony Wibowo (Telcomatics, 2019)
This study aims to determine whether using blind test method able to tell that the average person can differentiate the photos that were taken with DSLR camera, mirrorless camera, and smartphone camera. Aside from using blind test method, this research also used qualitative research method where we collected the data through online distribution by utilizing google form and social media application called line in distributing questionnaires to the social media line group chat of UIB majoring in Information System class of 2015 which were estimated about 140 people. In filling out the questionnaire there were 30 students who fill out the online questionnaire that had been distributed. The result of this research is that the respondents still cannot distinguish the difference of photos taken by DSLR camera, mirrorless camera, and smartphone camera. Majority of people are still unable to point out distinctively to understand the results of those three. This could be the result of the technological advancement of photography tools already advanced so far, so that common tool can produce results that can’t be discerned from professional tool.